The Effect of Customer Value, Trust, and Customer Satisfaction on Customer Loyalty Mediated By Customer Engagement (Empirical Study: Customer Music Course In Jakarta) - Hernando, Hernando; Bambang Sugiyanto , Liem (Asian Journal of Social and Humanities, 2024)
This study aims to investigate the impact of customer value, trust, and customer satisfaction on customer loyalty, with customer engagement as a mediating variable, focusing on music course customers in Jakarta. Utilizing a quantitative approach, data was collected from 95 respondents who have been customers of music courses for more than three months and are over 18 years old. The data was analyzed using Partial Least Square (PLS) with the SmartPLS 3.0 software. The results of the study indicate that trust and customer value positively and significantly influence customer engagement, which in turn significantly enhances customer loyalty. However, customer satisfaction did not show a significant direct effect on either customer engagement or customer loyalty. Additionally, while customer engagement mediates the relationship between customer value and customer loyalty, it does not mediate the relationship between trust or customer satisfaction and customer loyalty. The findings suggest that building customer engagement through perceived value can strengthen loyalty among music course customers. Limitations of this study include a focus on a specific geographic location (Jakarta) and the relatively small sample size, which may affect the generalizability of the results.